(untitled) (REMUNOM, 2024)
The analysis of parasites in lettuce from open-air markets is a crucial practice for ensuring food safety and public health. Lettuce, which is often consumed raw, can be a source of contamination by various parasites, including protozoa of the genus Entamoeba. The detection of these parasites is essential for preventing disease outbreaks and protecting consumer health. The study aims to investigate the presence and quantity of protozoa of the genus Entamoeba in lettuce samples sold in open-air markets in two cities in the high sertão region, using the Hoffman method to qualify the present protozoa. Detection includes ensuring safe food, protecting public health, complying with regulatory standards, implementing appropriate agricultural practices, and promoting education and awareness. Of the samples analyzed, 65% contained protozoa of the genus Entamoeba, indicating a high prevalence in the lettuce from the open-air markets during the study. The data highlight the need for further studies on Entamoeba contamination in water used for washing food. Although microscopy and concentration techniques are effective, continued research is necessary to improve the sensitivity and specificity of these methods.